TI_GERICHTE 11.2008.125 vom 23. März 2009 , Appello stralciato dai ruoli per mancato pagamento dell'anticipo - TI Tribunale d'appello (2009)
Appello stralciato dai ruoli per mancato pagamento dell'anticipo